In-vitro rooting and plantlet growth in sugarcane (Saccharum officinarum) - MANNAN, MANNAN; AMIN, AMIN (The Indian Journal of Agricultural Sciences, 2013)
Halfstrength Murnshige and Skoog medium was used as basal medium for plantlet fOlmation. Roots were fOrmed on separated individual shoots/tiller by their transfer on to 1/2 modified Murashige and Skoog medium containing 0.1,0.2,0.5 and 1.0 mg/litre levels of indole 3 acetic acid, indole 3 butyric acid and I naphthalene acetic acid. Maximum 96% rooting was obtained on 1/2 modified Murashige and Skoog medium with the combination 0.5% mg/litre indole 3 butyric acid + 0.5% me/litre I naphthalene acetic acid, whiCh on an average produced 8.33+ O33 and 9.0+0.9 number of roots/litre and length of roots were 1.14 + 0.22 cm and 1.50 + 0.50 cm for ’Isd 16’ and ’I 327-86’ of sugarcane (Saccharum officinarum L.), respectively.